The Nature of State - QUOC, DR. NGUYEN ANH; HOANG, DINH THE; CHIEN, DR. DINH VAN; THANH, DANG VIET (The journal of contemporary issues in business and government, 2021)
Human nature is shown in relation to its products. Human products are not only life, but also all that are perceived, created, produced for exchange and connection that make the human attribute common in all things. Human value is a constant that acts as a common parity in product exchange and connection, and the value of products is inversely proportional to each other. When using products as a common parity for exchange and connection between people, people become goods, the deception of this common equal makes the injustice between people appear. When using the falseness of standards, laws, and money as a common equal in exchange makes injustice appear more profound, the state appears to be a fair need of citizens. When the falsehood of norms, laws, and money as common parity is discovered by citizens, the existence of the state is only a means of making a living of officials and educators. The abolition of state protection, support for false officials and fake teachers is indispensable. Communism is fully expressed in the fulfillment of human nature, which is a natural developmental process.